KEPEMIMPINAN MANAJER KOPERASI SEKOLAH SEBAGAI PENGGERAK PENGEMBANGAN WIRAUSAHA - Sely Nur Anjani; Fatonah Setiyani; Mona Asiva Rahma; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the role of school cooperative managers’ leadership in fostering students’ entrepreneurial development through effective cooperative management. The cooperative serves as a practical learning medium for students to manage businesses, make decisions, and develop creativity, despite facing challenges such as limited competencies, capital, participation, and governance. Leadership plays a strategic role in aligning organizational goals, building an entrepreneurial culture, and creating a collaborative environment through appropriate styles such as democratic, transformational, and servant leadership. This research employs a qualitative approach using library research and finds that managerial leadership is essential in formulating vision, developing work programs, and optimizing cooperatives as sustainable entrepreneurship laboratories.